Find the Word! — But Where?: Maturana’s ‘Coordination’ and Sartre’s ‘Reflection’ around Naming - Imoto, Seiichi (Frontiers in Psychology, 2015)
‘Behavioral coordination’ theory of language of Maturana (1928–) does not give a clear explanation for the questions of how naming takes place and where a word adequate for our experience comes from. This flaw may be alleviated by Sartre (1905–1980)s ‘reflection’ theory. According to Sartre’s theory, we can make two types of sentences from the same data: for example, “I am conscious of this chair” and “There is consciousness of this chair.” The difference between the two sentences is the existence of ‘I’ in the first or its lack in the second. Where did ‘I’ come from or how was it removed? There must be a field in which ‘I’ is brought forth, and it may also be a field where naming can take place. This essay concerns a naming process with special reference to Sartre’s philosophy. At first, Maturana’s biology and his linguistic theory are explained, and Sartre’s fundamental ontology and in relation to this, his theory of reflection (two types of reflection) are introduced. Next, Sartre’s notions of language (words and naming) are explained. Then, after operational correspondences between Maturana’s ‘coordination’ and Sartre’s ‘reflection’ are examined, our primary questions are answered. Finally, constraints burdened on our cognition with language and the possibility of liberation from them are discussed. Main arguments: (1) Maturana’s ‘coordination’ and Sartre’s ‘reflection’ are operationally equivalent concepts; (2) Sartre can complement Maturana’s languaging theory of naming by providing both the domain for naming (the domain for the synthesis of identification, or for universalizing synthesis) and a mediator of naming (the cogito, namely the consciousness, of a languaging person).